Trilemma to Quadrilemma: An empirical study from Indonesia - Sri Andaiyani; Ariodillah Hidayat; Fida Muthia; Nona Widharosa; Mardalena Mardalena (Jurnal Ekonomi Pembangunan, 2020)
The objective of this study is to test the trilemma and the quadrilemma monetary policy using Indonesia data with covering years 1983 – 2017. The research suggest that the monetary independence and capital account openness might have been more passionately pursued by Bank Indonesia for testing the trilemma; while testing of the quadrilemma, the concentration seems to have shifted to take a middle position within each policy objectives. In this study, the full sample period is split in three subsamples: 1983-2017, 1983 – 1999 and 2000 – 2017. The methodology used in this research is ordinary least square. Our findings show that the policy might have shifted from exchange rate stability, capital account openness and foreign reserves in the first subsample to other four policy objectives in the second subsample. It indicates that foreign reserve plays as fourth objective leading the central bank to achieve at the same time the three “impossible” goals. Therefore, taking into account foreign reserve as a monetary policy objective is deserved. Adequacy of reserves could higher our capacity to prevent or mitigate external shocks.